Exploring genetic variability, heritability, and trait correlations in gari and eba quality from diverse cassava varieties in Nigeria - Aghogho, C.I.; Kayondo, S.I.; Maziya-Dixon, B.; Eleblu, S.J.; Asante, I.; Offei, Samuel Kwame; Parkes, Elizabeth Y.; Smith, A.I.; Adesokan, M.; Abioye, R.; Chijioke, Alamu Ugo; Ogunpaimo, K.; et al. (Wiley, 2024)
BACKGROUND Gari (especially in Nigeria) is an important West African food product made from cassava. It is an affordable, precooked, dry, easy to prepare and store food product. Eba is a stiff dough produced by reconstituting gari in hot water. Gari and eba quality is an important driver of varietal acceptance by farmers, processors, and consumers.